Horizontal and vertical variability of observed soil temperatures. (June 2017) - Illston, Bradley G.; Fiebrich, Christopher A.
Abstract : Two datasets of soil temperature observations collected at Norman, Oklahoma, USA, were analysed to study horizontal and vertical variability in their observations. The first dataset comprised 15‐min resolution soil temperature observations from 20 September 2011 to 18 November 2013 in seven plots across a 10‐m transect. In each plot, sensors were located at depths of 5, 10, and 30 cm. All seven plots observed fairly consistent maximum soil temperature observations during the spring, fall, and winter months. Starting in late May, the observed spread in soil temperatures across the 10‐m transect increased significantly until August when the observed spread in temperatures decreased. The range of observed minimum soil temperature was more consistent year‐round at the shallower depths, but showed similar patterns to the maximum soil temperature ranges at deeper depths. The second dataset comprised 15‐min resolution soil temperature observations from 20 November 2013 to 1 December 2015 in a single plot at the same location as the first dataset. Soil temperature sensors were placed every 2 cm from the surface down to 40 cm deep to study the vertical variability in soil temperature measurements (focusing on a winter and a summer case). Both winter and summer conditions showed that the temperature differences between depths behaved logarithmically with the shallower depths having larger differences than deeper depths.